PENGARUH AIR REBUSAN DAUN SALAM TEHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI DUKUH JANGKUNG REJO NOGOSARI BOYOLALI - Tunjung Sri Yulianti; Rahayu Setyaningsih; Mega Suryaningsih (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2014)
AbstractBackground: Hypertension or high blood pressure is an abnormal increase in blood pressure in the arteries continuously over a period. Hypertension today turned out to have a tendency to be one public health problem, especially in developed countries. The prevalence of hypertension in Indonesia amounted to 31.7% of the total adult population. Hypertension has no symptoms or signs typical as early warning, most people feel healthy despite having hypertension, is a dangerous situation because it can cause sudden death. Today many people are turning to herbs for the treatment of hypertension and one of the herbs used are bay leaves. The purpose of this study was to determine the effect of consumption of bay leaf decoction to decrease blood pressure in people with hypertension in Hamlet Tall rejo, Nogosari, Boyolali. This research method is a quasi-experimental research or quasi experiment with pre-post experimental design with a number of respondents 28 respondents hipetensi patients who did not use modern medicine to drink boiled water 2 times a day leaves every half a glass. The data are measured systolic and diastolic blood pressure in units of mm Hg and in analysis using test